PENGARUH KARAKTERISTIK WEBSITE, KARAKTERISTIK DAN DEMOGRAFI KONSUMEN TERHADAP KEPERCAYAAN PADA WEBSITE - Demitrius Kristiyono (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
Technological advance is giving impact on economic activity. Internet represents a popular device to be used in the online transaction. Indonesian understands that the potential of internet is profitable to be developed. However, local players of Indonesia fail to recognize this. Reluctance of Indonesian consumers to online transaction is interesting to be observed. Online transaction needs consumer trust because online transaction is different from offline transaction. Trust onto online transaction is different from trust onto offline transaction. Main object in the trust onto online transaction is website, internet or technology. The relationship of trust between seller and consumer cannot be separated from consumer characteristic because the interest to trust others needs motivational support and belief that others do not harm or mislead any conditions. Consumer trust represents a complex decision because it relates to the temporary demand of different individual based on its demography. Result of t-test on variable (X1) is that website characteristic variable has t-count of 2.365 and significance rate of 0.05. It supports the estimation that the website characteristic has obvious effect. The characteristic of consumer motivation (X2) in the online purchase in t-test has t-count of 2.135 but with significance rate below 0.05 to prove that consumer characteristic has significant effect on consumer trust. Consumer demography (X3) includes sex, respondent age, education background, expense rate, and interest in the t-test. All of the demographic items indicate that t-count is 3.257 with significance rate below 0.05 such that consumer trust is obviously affected